Techno-Economic Evaluation of Hyaluronic Acid Drugs Production Through Repeated Batch Fermentation Method using Streptococcus zooepidemicus - Intan Yustia; Brigitta Stacia Maharani; Gabriela Chelvina Santiuly Girsang; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (Media Pendidikan Gizi dan Kuliner, 2021)
Hyaluronic acid (C14H21NO11)n is one of the drugs components, a natural polysaccharide compound that makes up connective tissue and is soluble in water. HA can be applied in cosmetic, biomedical, and food industries. The purpose of this study was to determine the feasibility of a hyaluronic acid manufacturing project through repeated batch fermentation using Streptococcus zooepidemicus and then evaluating from an engineering and economic perspective. Engineering analysis was analyzed based on the available tools and raw materials in online web. The economic analysis was done using several economic parameters, such as the length of time required for an investment to return the total initial expenditure (PBP), the condition of a production project in the form of a production function in years (CNPV), project benefits and so on. The results showed that the production of Hyaluronic Acid nanoparticles was very prospective. Technical analysis to produce 86.4 g/liter of HA nanoparticles per day shows the total cost of the equipment purchased to be 7,264.51 USD. PBP analysis shows that investment will be profitable after more than three years. This project can compete with PBP capital market standards because of the short investment returns. To ensure the feasibility of a project, the project is estimated from ideal conditions to the worst case in production, including labor, sales, raw materials, utilities, and external conditions. The analysis concluded that the present project for the production of Hyaluronic acid nanoparticles is prospective in small scale industry and profitable (by positive values in all economic parameters).